AN EXAFS STUDY OF SOLVATION AND ION PAIRING IN AQUEOUS STRONTIUM SOLUTIONS TO 300°C - Seward T.M.; Driesner T.; Henderson C.M.B.; Charnock J.M. (My University, 1999)
X-ray absorption fine structure (EXAFS) measurements on 0.10-m strontium-containing solutions from 25 to 300°C at saturated vapour pressure indicate that the first shell Sr2+–oxygen (water) bond length decreases from 2.57 to 2.52 (±0.01) Å. Over the same temperature range, the number of coordinated first shell water molecules decreases from 8 to 6. Simulations of a 1.35-m SrCl2 using both rigid (SPC) and flexible (BJH) water models over the range from 25 to 330°C also show a decrease in the Sr2+–oxygen distance of 0.03 Å, which is independent of density. EXAFS measurements and molecular dynamics simulations of concentrated SrCl2 solutions up to 270°C and 300°C, respectively, show the presence of polynuclear cluster molecules, further underlining the importance of such species in defining the solute chemistry of hydrothermal solutions in the earth’s crust. These data represent the first direct spectroscopic confirmation of solute clustering in high temperature aqueous solutions of alkali metal or alkali earth metal salts.